Palaeomagnetic study of cenozoic rocks cropping out in the Southern Puna: New data on tectonic rotations - Prezzi, C.B. (2001)
In the Central Andes of southern Bolivia, northern Chile and north-western Argentina, a pattern of clockwise vertical axis rotations has been palaeomagnetically determined in Mesozoic and Cenozoic rocks cropping out in the Andean fore-arc and back-arc. The origin of these rotations is controversial. The scarcity of palaeomagnetic data available for the southern Central Andes, in particular for the Argentine Puna, is one of the problems that prevents the determination of the processes leading to the rotation pattern. With the aim of obtaining new palaeomagnetic data and trying to define the local or regional character of the rotations, 73 oriented samples were collected in the zones of Juncal Grande (25° 50′S - 67° 40′W) and Chorrillos (24° 12′S - 66°35'W), southern Argentine Puna. Remanent magnetizations, which indicate the existence of non-rotated and clockwise rotated localities, were isolated. It is suggested that the observed vertical axis rotations are of local character, controlled by the kinematics of the local structures.